ENHANCE VOCABULARY SKILL THROUGH READING REPETITION (REPEATED READING) - SEVENTILOFA, I GUSTI NGURAH OCTOVA (GANEC SWARA, 2021)
This research is an example of applied research. The aim of applied research is to increase scientific knowledge with a practical aim. In other words, the results of applied research will be immediately used for other practical purposes. The samples of this research are private class students who are taught English directly by the researcher. The number of samples of this research is 4 students who sit in grades 9 to 12 in high school. The research method used is observation, evaluation, and direct-interviews with the samples, then the data obtained are analyzed comprehensively. The result of this research; it is correct that by using the reading repetition strategy can improve the English vocabulary skills of the samples that have been appointed